Women Empowerment and Intra-household Dietary Diversity in Nigeria - Belmondo V. Tanankem; Uchenna R. Efobi; Ngozi S. Atata (African Governance and Development Institute (AGDI), 2016)
This study used a nationally representative survey from the 2012-2013 World Bank's General Household Survey for Nigeria, to examine the relationship between empowerment, measured using a modification of the Alkire et al. (2013) empowerment index, and household dietary diversity, based on the FAO groupings of food intake within the household. Accounting for potential endogeneity of empowerment, as well as using both the non-parametric regression and the traditional least square regression, we find that increases in empowerment are positively associated with household dietary diversity. Overall, household that are female biased in terms of share of female within the household, and those that favour female leadership tend to have higher significant improvement in their dietary intake with empowerment. On the contrary, empowerment generates a small proportion of male dietary diversity.
Keywords: Q01; Q18; R14; 330; Agriculture; Food Diversity; Food Security; Gender; Household; Nigeria; Rural Development